THE SPECIAL PLACE AND ESSENCE OF HABIB SADULLA’S POETRY IN CLASSICAL LITERATURE - A.Muhtorjonov (Research Focus International Scientific Journal, 2024)
A general classification of Habib Sa’dulla’s classic poems is given in this article.